CIRCULAR ECONOMY MODEL IN INDUSTRIAL ECOSYSTEMS - Roleders , V.V. (The actual problems of regional economy development, 2023)
The purpose of the article is to determine the stages, mechanisms and competitive advantages of the transformation of industrial ecosystems to the circular economy model. The methodological basis of the research is the method of scientific knowledge and system approach, comparison, analytical method, as well as dialectical, structural and functional methods. It has been proven that a closed ecological and economic cycle includes the achievement of sustainable economic growth through the use of global resources and the reuse of materials. It was determined that in the circular economy, companies develop integrated supply chains, using resources more efficiently and creating new markets. The stages of the organization of the reconstruction of ecosystems: the assessment of ecosystem readiness and its transformation are considered, it is found that innovative technologies contribute to the systemic implementation of changes. The transformation of ecosystems is carried out with the help of mechanisms for limiting early investment costs, investing in IT infrastructure, and encouraging stakeholders to cooperate. It is proven that the riskiness of the transformed business model forces the parties to agree on the distribution of risks and revenues. The principles of a circular ecological and economic cycle, which is based on circular development and reuse of waste, were proposed. The basis of the proposed scheme of principles reconstructs a simple economic linear scheme, which was previously based on the principles of "extracted - processed - consumed - discarded waste". To change the linear economy to the economy of a circular ecological and economic cycle, there is a need to ensure the maximum efficiency of each stage of the life cycle of a product or service. As part of the development of the circular ecological-economic cycle economy model, a conceptual approach to the introduction of a circular economy in Ukraine was proposed. The transformation of industrial ecosystems can provide enterprises with various competitive advantages. Among the most common strategic advantages are differentiation and cost leadership. However, the main benefit of ecosystem transformation is to enhance the ability of ecosystems to achieve good triple bottom line outcomes, delivering social, financial and environmental benefits to clients. In particular, companies achieve higher productivity, better use of resources, reduction of hazardous jobs, greater transparency of the ecosystem, market growth and financial returns. The transformation of the ecosystem to a circular economy model creates opportunities for the development of sustainable industry.